LAMINATE AND METHOD FOR MANUFACTURING LAMINATE

By forming an active energy radiation hardenable resin layer on the substrate and performing dry treatment to form a cover layer, the problem of surface inhomogeneity control is solved and the anti-stickness and optical performance are improved.

JP7661676B2Active Publication Date: 2025-04-15MITSUBISHI CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020057970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2025-04-15
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

In the prior art, when surface inhomogeneity is formed, it is difficult to control the shedding of surface particles, resulting in the inclusion of foreign matters in the packaging material, and there is a lack of effective methods to control the uneven structure.

Method used

Using the active energy radiation-hardenable resin composition, a resin layer is formed by forming a resin layer on the matrix and dry treatment on the resin layer, and the surface treatment is controlled to control the semi-hardened state of the resin layer to form a surface unevenness of the natural wrinkle structure.

Benefits of technology

The controllability of surface inhomogeneity is achieved, particles are avoided, and anti-stickness and optical properties of packaging materials are improved, such as controlling light scattering and light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661676000002
    Figure 0007661676000002
  • Figure 0007661676000003
    Figure 0007661676000003
  • Figure 0007661676000004
    Figure 0007661676000004
Patent Text Reader

Abstract

To provide a laminate having surface unevenness which has controllable shape and in which there is no risk that particles fall off.SOLUTION: A laminate 10 has a base material 11, and a resin layer 12 provided on at least one surface 11A of the base material 11, wherein the resin layer 12 is formed of an active energy ray-curable resin composition, an outermost surface 10A of the laminate 10 on one surface 11A side of the base material 11 has unevenness, and the active energy ray-curable resin composition contains no active energy ray polymerization initiator or contains 2.5 mass% or less of the active energy ray polymerization initiator.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having an uneven surface, and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, techniques for forming minute irregularities on the surfaces of various materials have been developed. For example, in packaging materials, it is known to form irregularities on the lid material or the inner peripheral surface of the container in order to prevent the contents from adhering to the material. In addition, a technique is also known in which fine irregularities are formed on optical materials to increase the haze and suppress transmission or surface reflection. For each of these applications, there is an optimum surface unevenness structure, and the unevenness structure is formed by controlling it.

[0003] Patent Document 1 discloses a water-repellent laminate comprising, in this order, a substrate, an organic solvent-resistant sealant film layer, and an anti-adhesion layer, the anti-adhesion layer containing a thermoplastic resin, water-repellent fine particles, and bead particles having an average particle size larger than that of the water-repellent fine particles. It has been shown that such a laminate has an anti-adhesion layer that contains two types of particles of different sizes, which forms a unique uneven structure on the surface, thereby significantly improving the anti-adhesion and water repellency of viscous contents. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-226199 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, as disclosed in Patent Document 1, when unevenness is formed by particles, it is impossible to prevent the particles present near the surface from falling off. For example, when used as a packaging material, it is prone to foreign matter being mixed into the contents, making it difficult to apply the method to anything other than a lid material. Furthermore, Patent Document 1 does not specifically disclose a method for controlling the concave-convex structure, and further improvements are required for controlling the concave-convex structure.

[0006] Therefore, an object of the present invention is to provide a laminate having surface irregularities which can be controlled and which is free from the risk of particles falling off. [Means for solving the problem]

[0007] The gist of the present invention is as described in [1] to

[11] below. [1] A substrate and a resin layer provided on at least one surface of the substrate, the resin layer is formed from an active energy ray-curable resin composition, the outermost surface of the laminate on the one surface side of the base material has projections and recesses; A laminate, wherein the active energy ray-curable resin composition does not contain an active energy ray polymerization initiator or contains an active energy ray polymerization initiator in an amount of 2.5 mass % or less. [2] The laminate according to the above [1], wherein the active energy rays are ultraviolet rays. [3] The laminate according to the above [1] or [2], wherein the outermost surface has an arithmetic mean roughness (Sa) of 50 nm or more. [4] The laminate according to any one of the above [1] to [3], further comprising a cover layer on the resin layer. [5] The laminate according to the above [4], wherein the cover layer is an inorganic substance-containing layer. [6] The laminate according to the above [5], wherein the inorganic substance-containing layer is formed from at least one material selected from the group consisting of DLC, metals, metal oxides, metal nitrides, metal carbides, and composites thereof. [7] The laminate according to any one of the above [4] to [6], wherein the cover layer has a thickness (ta) of 5 nm or more and 300 nm or less. [8] A step of applying an active energy ray-curable resin composition to at least one surface of a substrate to form a resin layer precursor; a step of further performing a surface treatment on the semi-cured or uncured resin layer precursor by a dry process to form irregularities on one surface of the substrate; Equipped with The method for producing a laminate, wherein the active energy ray-curable resin composition does not contain an active energy ray polymerization initiator or contains an active energy ray polymerization initiator in an amount of 2.5 mass % or less. [9] The method for producing the laminate described in [8] above, wherein a cover layer is formed by the dry process.

[10] The method for producing a laminate according to the above [8] or [9], wherein the surface treatment is any one of chemical vapor deposition, physical vapor deposition, and plasma treatment.

[11] A step of semi-curing the resin layer precursor formed by the coating, The method for producing a laminate according to any one of the above items [8] to

[10] , wherein the surface treatment is carried out on the semi-cured resin layer precursor. Effect of the Invention

[0008] The present invention can provide a laminate having surface irregularities which can be controlled and which is free from the risk of particles falling off. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Figure 4] 1 is a schematic diagram showing an example of a laminate of the present invention. [Diagram 5] 2 is a three-dimensional image obtained by observing the outermost surface of the laminate of Example 1 using a three-dimensional non-contact surface shape measuring device. [Figure 6]1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Example 2 using a three-dimensional non-contact surface shape measuring device. [Figure 7] 1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Example 3 using a three-dimensional non-contact surface shape measuring device. [Figure 8] 1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Example 4 using a three-dimensional non-contact surface shape measuring device. [Figure 9] 1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Comparative Example 2 using a three-dimensional non-contact surface shape measuring device. [Figure 10] 1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Comparative Example 4 using a three-dimensional non-contact surface shape measuring device. [Figure 11] 1 is a three-dimensional image obtained by observing the outermost surface of the laminate of Comparative Example 5 using a three-dimensional non-contact surface shape measuring device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Next, the present invention will be described in detail based on the embodiments of the present invention, but the present invention is not limited to the embodiments described below.

[0011] A laminate 10 according to one embodiment of the present invention has a substrate 11 and a resin layer 12 provided on at least one surface 11A of the substrate 11, and the resin layer 12 is formed from an active energy ray-curable resin composition, for example, as shown in FIGS.

[0012] In the laminate 10, no other layer may be provided on the resin layer 12, and the resin layer 12 may be the outermost surface 10A of the laminate 10 on one surface 11A side of the substrate 11, as shown in Fig. 1. In addition, in the laminate 10, it is preferable that a cover layer 13 is provided on the resin layer 12, as shown in Figs. 2 and 3, and an overcover layer 14 may be further provided on the cover layer 13, as shown in Fig. 3. When cover layer 13 is provided and overcover layer 14 is not provided on cover layer 13, cover layer 13 forms outermost surface 10A of laminate 10, as shown in FIG. Furthermore, when an overcover layer 14 is further provided on the cover layer 13, the overcover layer 14 forms the outermost surface 10A of the laminate 10, as shown in FIG. In the laminate 10, the resin layer 12 may be formed on the substrate 11 so as to be in direct contact with the substrate 11, or a layer such as an adhesive layer may be appropriately provided between the substrate 11 and the resin layer 12. The laminate of the present invention will be described in more detail below.

[0013] <Unevenness of the top surface> In the laminate 10, the outermost surface 10A of the laminate 10 on one surface 11A side of the base material 11 has projections and recesses. The laminate 10 has projections and recesses and is therefore applicable to various applications that utilize the fine projections and recesses on the surface (such as adhesion prevention and light transparency). For example, if a liquid-repellent material is selected for the layer constituting outermost surface 10A of laminate 10, contents will not easily adhere to the surface of the laminate, making it applicable to packaging materials. Furthermore, if the adhesion of cells, bacteria, etc. can be reduced by controlling the uneven structure, it may be possible to apply the material to sanitary materials. Furthermore, by having the unevenness, good fogging properties can be achieved, and for example, the haze and light transmittance of the laminate can be controlled.

[0014] The unevenness of the outermost surface 10A preferably has a wrinkle structure. By having unevenness including a wrinkle structure, the laminate 10 can be easily applied to various applications (such as adhesion prevention and light transmission) that utilize fine unevenness on the surface. In addition, by having the unevenness with a wrinkle structure, the laminate can easily exhibit adhesion prevention performance and also easily control light transmission. The wrinkle structure is a wrinkled shape caused by the buckling of the resin layer 12, and is different from the uneven shape with many dot-like protrusions, such as the uneven shape formed by particles. In this embodiment, the unevenness is formed by the buckling of the resin layer itself, so that an uneven surface without the risk of particles falling off can be formed. In addition, since this wrinkle structure is formed spontaneously, a mold such as a transfer sheet is not required.

[0015] A schematic diagram of the wrinkle structure is shown in Figure 4. The wrinkle structure is composed of a plurality of ripples c, and each of the plurality of ripples c has a protrusion a and a groove b. The protrusion a and the groove b each have a straight line, a curved line, or a combination of these. The protrusion a is formed irregularly. The protrusion a may be formed continuously or discontinuously.

[0016] As described below, the wrinkle structure is formed when compressive stress is applied along the surface direction to the resin layer 12. It is presumed that the compressive stress is applied along multiple directions along the surface direction, which results in the irregular formation of the protrusions a and grooves b. The presence or absence of a wrinkle structure can be confirmed by observation with a microscope such as a scanning electron microscope (SEM) at a magnification of, for example, about 1,000 to 100,000 times, or by three-dimensional images obtained by a three-dimensional non-contact surface profile measuring instrument (see Figs. 5 to 8). When a wrinkle structure is present, the protrusions a and grooves b appear to form undulations c. The undulations c can be observed in either a square or rectangular observation image with a side of, for example, about 3 to 500 µm, preferably about 4 to 100 µm. The protrusions a forming the wrinkle structure are irregular, and the undulations c also appear at a period on the order of micrometers. Therefore, as shown in Figures 5 to 8, the undulations c formed by the protrusions a and grooves b appear as multiple peaks of the protrusions a and multiple bottoms of the grooves b (e.g., five or more times) even when viewed in multiple directions (e.g., three directions) such as the vertical, horizontal, and diagonal directions in the observed image. The period of the undulations c is typically not constant, and therefore the distance between the peaks of the protrusions a and the distance between the bottoms of the grooves b are also not constant. The "period of waviness c" refers to the distance d between the apex of a protrusion a and the apex of the protrusion a adjacent to a groove b adjacent to the protrusion a, as shown in FIG.

[0017] The fact that the unevenness of outermost surface 10A of laminate 10 has a spontaneously formed wrinkle structure is reflected in, for example, the value of Ssk (skewness). Ssk is a parameter that indicates the degree of deviation of the surface unevenness. This deviation Ssk represents the cube mean of Z(x,y) on a reference plane that has been made dimensionless by the cube of the root-mean-square height Sq, and means skewness, a value that indicates the symmetry of the peaks and valleys centered on the average plane. Therefore, when the deviation Ssk<0, it means that there is a downward deviation from the average line, that is, there are more concave valleys than convex peaks. On the other hand, when Ssk>0, it means that there is an upward deviation from the average line, that is, there are more convex peaks than concave valleys. And when the deviation Ssk=0, it means that there is symmetry (normal distribution) with respect to the average line.

[0018] The wrinkle structure of the outermost surface 10A of the laminate 10 of the present invention is a wrinkled shape caused by buckling of the resin layer 12. Therefore, compared to the uneven shape formed by particles, the symmetry of the convex peaks and concave valleys is higher. Therefore, it is considered that the Ssk of the wrinkle structure of the laminate 10 of the present invention is closer to 0 than the Ssk of the uneven shape formed by particles. From this viewpoint, the absolute value of Ssk of the outermost surface 10A of the laminate 10 is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less, and even more preferably 0.8 or less. Furthermore, among these, it is preferably 0.5 or less, more preferably 0.3 or less, and even more preferably 0.1 or less.

[0019] Ssk is a parameter based on ISO25178 and can be calculated, for example, by the following method. Measurements are taken using a three-dimensional non-contact surface shape measuring device (VertScan2.0 R5200G, manufactured by Ryoka Systems Co., Ltd.) with a CCD camera SONY HR-50 1 / 3 inch (objective lens 10x to 50x, wavelength filter 530nm white) in measurement mode; Wave. The attached analysis software (VS-Viewer Version 5.1.3) uses polynomial fourth-order approximation surface correction to remove waviness components from the captured image, and then performs interpolation processing (processing to compensate for pixels for which height data could not be obtained using height data calculated from surrounding pixels) to calculate the height.

[0020] The outermost surface 10A of the laminate preferably has a specific surface area (S / A) of 1.003 or more. By making the specific surface area 1.003 or more, it means that the surface area is sufficiently large due to the uneven structure. Therefore, in optical applications, cloudiness is easily manifested, and the haze value of the laminate can be adjusted by adjusting the specific surface area. From these viewpoints, the specific surface area (S / A) is more preferably 1.01 or more, further preferably 1.05 or more, and even further preferably 1.1 or more. In addition, the specific surface area (S / A) is not particularly limited, but in order to prevent the convex parts of the uneven structure, such as the protrusions of the wrinkle structure, from becoming too high, thereby reducing the structural strength, the specific surface area is preferably 2 or less, more preferably 1.7 or less, and even more preferably 1.5 or less. The specific surface area (S / A) can be calculated by S / A, where A is the area of ​​the measurement target area on the outermost surface 10A and S is the surface area of ​​the measurement target area.

[0021] The Sa (arithmetic mean roughness) of the outermost surface 10A of the laminate is not particularly limited, but is, for example, 50 nm or more. By making Sa 50 nm or more, it means that sufficient unevenness is formed, and if applied to, for example, optical materials, the haze can be adjusted. From these viewpoints, Sa (arithmetic mean roughness) is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 300 nm or more. Furthermore, the arithmetic mean roughness Sa is not particularly limited, but from the viewpoint of maintaining the physical strength of the uneven structure, it is preferably 3000 nm or less, more preferably 1800 nm or less, and even more preferably 1300 nm or less.

[0022] The Sz (maximum height) of the outermost surface 10A of the laminate is not particularly limited, but is preferably 400 nm or more, more preferably 500 nm or more, and even more preferably 600 nm or more. If Sz is equal to or greater than these lower limits, it means that sufficient buckling has progressed and high convex parts have been formed. Therefore, for example, if it is applied to an optical material, it can adjust the haze. Sz (maximum height) is not particularly limited, but from the viewpoint of maintaining the physical strength of the concave-convex structure, it is preferably 20,000 nm or less, more preferably 15,000 nm or less, and further preferably 10,000 nm or less. Sa, Sz and the specific surface area (S / A) can be measured using a three-dimensional non-contact surface shape measuring instrument (VertScan2.0 R5200G, manufactured by Ryoka Systems Co., Ltd.) The measurement may be performed with a 50x objective lens in a range of, for example, 94.33 μm×70.75 μm.

[0023] As described above, the laminate can control the surface irregularity shape, and the haze value of the laminate can be controlled by adjusting the irregularity shape to exhibit good fogging properties. The haze value of the laminate is not particularly limited and can be adjusted appropriately depending on the application, but in order to exhibit good fogging properties, it is, for example, 15% or more, preferably 30% or more, and more preferably 40% or more. The haze value is not particularly limited in terms of the upper limit, and may be 100% or less. The haze value can be measured by the method described in the examples.

[0024] <Base material> The substrate used in the laminate of the present invention is not particularly limited, and examples of the material include organic substances such as resins, inorganic substances such as metals and metal oxides, and organic-inorganic composites. Examples of the shape of the substrate include sheets, films, substrates, and three-dimensional objects including containers and tubes. The substrate of the present invention is preferably made of a resin, and more preferably a resin film or a plastic container. The laminate of the present invention can easily form unevenness even on a substrate having a complex shape or on the inside of a container, by the manufacturing method described below.

[0025] [Resin film] The resin film used as the substrate is not limited in material and structure as long as it has necessary and sufficient rigidity. The resin film may be a single-layer structure or a multi-layer structure. When the resin film has a multi-layer structure, it may be a four-layer or more multi-layer structure in addition to a two-layer or three-layer structure as long as it does not impair the effects of the present invention.

[0026] Examples of resins used in the resin film include polyester, polyarylates, polyethersulfone, polycarbonate, polyetherketone, polysulfone, polyphenylene sulfide, polyester-based liquid crystal polymer, triacetyl cellulose, cellulose derivatives, polypropylene, polyamides, polyimide, polycycloolefins, etc. These resins may be used alone or in combination of two or more in the resin film. In addition, when the resin film is multi-layered, the resins constituting each layer may be different from each other or may be the same as each other. In addition, the resin film may be a single layer or a multilayer film, with each layer being constituted by combining two or more of the above resins.

[0027] Whether the resin film has a single layer structure or a multilayer structure, it is preferable that the resin film is a polyester film in which the main component resin of each layer is polyester. In this case, the "main component resin" means the resin that is contained in the largest proportion among the resins constituting the polyester film, for example, a resin that accounts for 50 mass % or more, preferably 70 mass % or more, and more preferably 80 mass % or more (including 100 mass %) of the resins constituting the polyester film. As long as each layer of the resin film contains polyester as a main component resin, it may contain a resin other than polyester or a component other than resin.

[0028] The polyester may be a homopolyester or a copolymer polyester. In the case of a homopolyester, it is preferable that the polyester is obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid. Examples of the aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol.

[0029] On the other hand, examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc.

[0030] Specific examples of polyester include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polybutylene naphthalate (PBN). Of these, PET and PEN are preferred, and PET is more preferred.

[0031] The resin film may contain particles for the purpose of forming a fine uneven structure on the film surface to impart various functions and for the main purpose of preventing the occurrence of scratches in each process. The type of the particles is not particularly limited as long as they are particles that can provide easy slipping. For example, inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin can be mentioned. These can be used alone or in combination of two or more. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst in a process for producing a resin component such as polyester can also be used. The shape of the particles is not particularly limited. For example, it may be any of spherical, blocky, rod-like, flat, etc. Furthermore, the hardness, specific gravity, color, etc. of the particles are also not particularly limited. Two or more kinds of these particles may be used in combination as necessary.

[0032] The average particle size of the particles is preferably 5 μm or less, more preferably 0.01 μm to 3 μm, and even more preferably 0.5 μm to 2.5 μm. By making the particle size 5 μm or less, the surface roughness of the resin film is prevented from becoming rough, and problems are less likely to occur when forming the resin layer and the cover layer.

[0033] The particle content is preferably 5% by mass or less, more preferably 0.0003% by mass or more and 3% by mass or less, and even more preferably 0.01% by mass or more and 2% by mass or less, based on 100% by mass of the resin film. By setting the particle content in this range, it is possible to achieve both smoothness and transparency of the film.

[0034] The method of adding particles to the resin film is not particularly limited, and any conventionally known method can be used. For example, the particles can be added during the process of producing the resin component. For example, in the case of a polyester film, the particles can be added at any stage of polyester production. It is preferable to add the particles after the esterification or transesterification reaction is completed.

[0035] If necessary, conventionally known additives such as antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, and ultraviolet absorbing agents may be added to the resin film.

[0036] The thickness of the resin film is not particularly limited as long as it is within the range in which a film can be formed, but is preferably 12 μm or more and 250 μm or less, more preferably 25 μm or more and 250 μm or less, and even more preferably 50 μm or more and 200 μm or less.

[0037] The resin film can be formed by, for example, forming a resin composition into a film shape by a melt casting method or a solution casting method. In the case of a multi-layer structure, it may be co-extruded. In addition, it may be uniaxially or biaxially stretched, and from the viewpoint of rigidity, a biaxially stretched film is preferable.

[0038] [Plastic containers] The plastic container used as the substrate in the present invention is not particularly limited, and may be a bottomed cylindrical container, or a container with a rounded bottom and an elliptical cross section. Also, it may be a container with a substantially rectangular cross section whose mouth is narrower than its body. The diameter of the mouth of the container may be narrower.

[0039] Examples of plastic materials that make up plastic containers include polyethylene terephthalate resin (PET), polyethylene terephthalate copolymer resin (copolymer resin using cyclohexanedimethanol or the like as a comonomer instead of ethylene glycol in the alcohol component of polyester), polybutylene terephthalate resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin (PP), cycloolefin copolymer resin (COC, cyclic olefin copolymer), ionomer resin, poly-4-methylpentene-1 resin, polymethyl methacrylate resin, polystyrene resin, ethylene-vinyl alcohol copolymer resin, acrylonitrile resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyamide resin, polyamideimide resin, polyacetal resin, polycarbonate resin (PC), polysulfone resin, tetrafluoroethylene resin, acrylonitrile-styrene resin, acrylonitrile-butadiene-styrene resin, etc., and among these, polyethylene terephthalate resin (PET) and polycarbonate resin (PC) are preferred in terms of versatility.

[0040] [Substrates other than resin] The substrate other than resin is not particularly limited as long as a resin layer (described later) can be fixed onto the substrate, but examples of the substrate include metals, semi-metals, ceramics, and composite materials. Examples of metals include aluminum, copper, silver, gold, iron, and nickel. These metals may be used alone or in the form of an alloy. Preferred examples include aluminum, copper, and the steel-based material SUS. Examples of the semi-metal include silicon and germanium, and these semi-metals may be used alone or in the form of an alloy. Ceramics include inorganic solid materials such as oxides, carbides, nitrides, and borides, and preferably include glass, ceramics, and the like. A composite material is a material that is an integral combination of two or more different materials such as resin, metal, semi-metal, and ceramic, and examples of the composite material include glass fiber reinforced plastic, carbon fiber reinforced plastic, and nanocomposite material. As the substrate other than these resins, metal containers, glass containers, etc. are suitable.

[0041] <Resin layer> The resin layer is formed from an active energy ray curable resin composition (hereinafter, sometimes simply referred to as "curable resin composition"). The resin layer is a cured product formed by curing the curable resin composition. By curing the curable resin composition, it can be easily adhered to a substrate, a cover layer, and the like. In addition, when a surface treatment is performed by a dry process in a semi-cured state, as described later, the resin layer buckles in response to a compressive stress acting along the surface direction, and an uneven shape, preferably an uneven shape having a wrinkle structure, can be formed.

[0042] [Curable resin composition] (Active energy ray polymerizable compound) The curable resin composition contains an active energy ray polymerizable compound. The active energy ray polymerizable compound is a compound that can be polymerized by irradiation with active energy rays. Details of the active energy ray are as described in the production method described later, but it is preferable that the active energy ray is ultraviolet light. That is, the active energy ray curable resin composition is preferably an ultraviolet light curable resin composition. The resin component of the resin layer formed from the curable resin composition can be a mixture of a prepolymer such as epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, or acrylic (meth)acrylate with an active energy ray-polymerizable monomer, or the active energy ray-polymerizable monomer can be used alone.

[0043] The active energy ray polymerizable monomer is not particularly limited as long as it is a compound having a radical polymerizable group, and examples thereof include polyfunctional active energy ray polymerizable monomers. The number of radical polymerizable groups contained in one molecule of the polyfunctional active energy ray polymerizable monomer is not particularly limited, and may be 2 or more. The radically polymerizable group includes functional groups containing a carbon-carbon unsaturated bond, such as a (meth)acryloyl group and a vinyl group, and among these, a (meth)acryloyl group is preferred.

[0044] Examples of the active energy ray-polymerizable monomer include polyfunctional (meth)acrylates having an aromatic ring. Specifically, polyfunctional (meth)acrylates having a benzene ring, a naphthalene ring, an anthracene ring, a fluorene ring, a phenanthrene ring, a phenalene ring, or the like are preferred. Among these, fluorene-based polyfunctional (meth)acrylates having a fluorene ring are preferred. Examples of fluorene-based polyfunctional (meth)acrylates include 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)-3-methylphenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxypropoxy)-3-methylphenyl]fluorene, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)-3,5-dimethylphenyl]fluorene. , 9,9-bis[4-((meth)acryloyloxypoly(ethyleneoxy))phenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypolyethyleneoxy)-3-methylphenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypoly(propyleneoxy))-3-methylphenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypoly(ethyleneoxy))-3,5-dimethylphenyl]fluorene, and the like.

[0045] In addition, as the active energy ray-polymerizable monomer, various polyfunctional (meth)acrylates can be used in addition to polyfunctional (meth)acrylates having an aromatic ring, and examples of such polyfunctional (meth)acrylates include aliphatic polyfunctional (meth)acrylates such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate. The above-mentioned active energy ray polymerizable monomers may be used alone or in combination of two or more kinds. Among the above, polyfunctional (meth)acrylates having an aromatic ring are preferred, and the polyfunctional (meth)acrylates having an aromatic ring may be used in combination with other active energy ray-polymerizable compounds. The active energy ray-polymerizable monomer may be used alone or in combination with a monofunctional active energy ray-polymerizable compound described below.

[0046] The active energy ray polymerizable monomer is not limited to polyfunctional, and may be a monofunctional active energy ray polymerizable monomer. The monofunctional active energy ray polymerizable monomer may be used alone, or may be used in combination with the polyfunctional active energy ray polymerizable monomer as described above. Examples of the monofunctional active energy ray polymerizable monomer include alkyl (meth)acrylates, cyclic alkyl (meth)acrylates, (meth)acrylates having an aromatic ring, hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, epoxy group-containing monomers, acrylamide compounds, (meth)acrylonitrile, styrene derivatives, and various vinyl halides such as vinylidene chloride.

[0047] Examples of the alkyl (meth)acrylate that can be used include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, pentadecyl (meth)acrylate, and dodecyl (meth)acrylate. Examples of the cyclic alkyl (meth)acrylate that can be used include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. Examples of the (meth)acrylate having an aromatic ring that can be used include phenyl (meth)acrylate, etc.

[0048] Examples of hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate. Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid. Examples of the amino group-containing monomer include dimethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)methacrylate, and diethylaminoethyl (meth)acrylate. Examples of the amino group-containing monomer include dimethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)methacrylate, and diethylaminoethyl (meth)acrylate. Examples of epoxy group-containing monomers include glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, α-methyl-o-vinylbenzyl glycidyl ether, α-methyl-m-vinylbenzyl glycidyl ether, α-methyl-p-vinylbenzyl glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate. Examples of the acrylamide compounds include (meth)acrylamide, diacetone acrylamide, and N-methylol acrylamide. Examples of the styrene derivative include styrene, α-methylstyrene, divinylbenzene, and vinyltoluene.

[0049] (Active energy ray polymerization initiator) In the present invention, the curable resin composition does not contain an active energy ray polymerization initiator, or if it contains one, the content is 2.5 mass % or less. As described below, the laminate of the present invention is one in which the unevenness is formed by carrying out a dry process on the curable resin composition in an uncured or semi-cured state. Therefore, since the curable resin composition is not completely cured at the stage of irradiation with active energy rays, the curable resin composition may not contain an active energy ray polymerization initiator or may contain a small amount of the active energy ray polymerization initiator, as described above. In addition, the curable resin composition does not contain an active energy ray polymerization initiator or the content is low, so that the sensitivity to active energy rays is low, and even if cured by irradiation with active energy rays, it is easy to keep the appropriate semi-cured state, and when unevenness is formed by the dry process described below, the unevenness can be sufficiently formed, and the shape of the unevenness can be easily controlled. Furthermore, by reducing the amount of active energy ray polymerization initiator, it is advantageous in terms of cost. On the other hand, if the content is more than 2.5 mass%, the polymerization reaction is likely to proceed by overcoming oxygen inhibition that hinders radical polymerization, and the curing proceeds too much by irradiation with active energy rays, so that the desired uneven shape cannot be formed by the dry process.

[0050] The content of the active energy ray polymerization initiator in the curable resin composition is preferably from 0 mass% to 2.0 mass% inclusive, more preferably from 0 mass% to 1.5 mass% inclusive, even more preferably from 0 mass% to 1.0 mass% inclusive, and still more preferably from 0 mass% to 0.7 mass% inclusive, from the viewpoint of maintaining an appropriate semi-cured state by irradiation with active energy rays and making it easier to control the uneven shape, and from the viewpoint of costs. In addition, the curable resin composition contains a certain amount or more of active energy ray polymerization initiator, so that the curing can be moderately promoted by the irradiation of active energy rays, and the stickiness of the surface of the resin layer precursor can be suppressed, and the handleability can be improved. From such a viewpoint, the content of the active energy ray polymerization initiator is more preferably 0.2 mass% or more and 1.0 mass% or less, and from the viewpoint of both the controllability of the uneven shape and the handleability, it is even more preferably 0.2 mass% or more and 0.8 mass% or less. The content of 0% by mass means that the curable resin composition does not contain an active energy ray polymerization initiator. The content of the active energy ray polymerization initiator is the content when the curable resin composition is taken as 100% by mass.

[0051] Examples of the active energy ray polymerization initiator include benzil; benzophenone derivatives such as benzophenone, 4-methylbenzophenone, 2-methylbenzophenone, 4,4'-bis(diethylamino)benzophenone, 2,4,6-trimethylbenzophene, and 4-phenylbenzophenone; 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-(3-dimethylamino- 2-Hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride and other thioxanthones; benzyl dimethyl ketals such as benzyl dimethyl ketal; 2-Hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl-phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxymethylpropan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2- α-Hydroxyalkylphenones such as methylpropan-1-one and oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone};α-Hydroxyacetophenones such as 2-hydroxyacetophenone;Hydroxyketones other than these;2-benzyl-2-dimethylamino-4-morpholinobutyrophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-methyl-1-[4-(methylthio)phenyl]-2-morph Examples of the arylphosphine oxide include aminoalkylphenones such as 2-(dimethylamino)-2-(4-methylbenzyl)-1-(4-morpholinophenyl)-butan-1-one; acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and oxime ester compounds. Among these, α-hydroxyalkylphenones are preferred because they are less likely to yellow when cured and give transparent cured products, and 1-hydroxycyclohexyl-phenyl ketone is particularly preferred. The active energy ray polymerization initiator may be used alone or in combination of two or more.

[0052] The curable resin composition may contain, as necessary, an internal antifoaming agent, a coatability improving agent, a thickener, an organic lubricant, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, inorganic particles, organic particles, etc., within the scope of the present invention. These additives may be used alone, or two or more kinds may be used in combination as necessary.

[0053] [Resin layer thickness] The thickness (tb) of the resin layer is not limited and may be adjusted according to the step of the unevenness to be formed and the application, but is preferably 0.1 μm or more and 15 μm or less. If it is 15 μm or less, peeling from the substrate due to the internal stress of the resin layer itself can be prevented. If it is 0.1 μm or more, the thickness of the resin layer can be kept uniform, and a certain level of roughness can be ensured by the unevenness. From this viewpoint, the thickness (tb) of the resin layer is more preferably 0.5 μm or more, even more preferably 1 μm or more, even more preferably 2 μm or more, and is preferably 10 μm or less, more preferably 7 μm or less. The thicknesses of the resin layer and the cover layer and overcover layer described below can be calculated by measuring the maximum thickness (convex peaks) and minimum thickness (concave valleys) through step measurement using a microprofile measuring device or cross-sectional observation using a scanning electron microscope (SEM) and / or a transmission electron microscope (TEM) and then calculating the average value of these.

[0054] <Cover layer> In the present invention, as described above, it is preferable to form a cover layer on the resin layer. The cover layer may be formed as a layer that is in direct contact with the resin layer. Specific examples of the cover layer include an inorganic substance-containing layer and a cover resin layer. Among these, an inorganic substance-containing layer is preferable. In the following description, the inorganic substance-containing layer constituting the cover layer is sometimes referred to as inorganic substance-containing layer (1) to distinguish it from the inorganic substance-containing layer constituting the overcover layer described below.

[0055] [Inorganic-containing layer (1)] The inorganic substance-containing layer (1) is a layer formed of an inorganic substance and contains an inorganic substance as a main component. Incidentally, containing an inorganic substance as a main component means that the inorganic substance occupies 50 mass% or more, particularly 70 mass% or more, particularly 80 mass% or more, particularly 90 mass% or more, particularly 100 mass% of the inorganic substance-containing layer. The inorganic substance-containing layer (1) is preferably formed of an inorganic substance that has good adhesion to the resin layer. In addition, the inorganic substance-containing layer (1) is preferably formed using a material that can be easily formed into a film on the resin layer by a dry process.

[0056] The inorganic substance-containing layer (1) is preferably formed from at least one inorganic substance selected from diamond-like carbon (DLC), metal, metal oxide, metal nitride, metal carbide, or a composite thereof. The metal here also includes so-called semimetals such as silicon, boron, and germanium. The inorganic substance may further contain a fluoride such as calcium fluoride, or may contain fluorine as described later. In the inorganic substance-containing layer (1), examples of the metal constituting the metal, metal oxide, metal nitride, metal carbide, or a composite thereof include silicon, aluminum, zinc, titanium, niobium, gold, silver, copper, indium, tin, nickel, and the like. Among these, silicon and niobium are preferred, and silicon is more preferred.

[0057] The inorganic substance used in the inorganic substance-containing layer (1) is preferably at least one selected from silicon-based compounds such as silicon oxide, silicon nitride, silicon oxynitride, silicon oxide carbide, silicon oxycarbonitride, silicon carbide, fluorine-containing silicon oxide, and fluorine-containing silicon carbide; aluminum-based compounds such as aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxide carbide; niobium-based compounds such as niobium oxide; zinc-based compounds such as zinc oxide; titanium-based compounds such as titanium oxide; diamond-like carbon, fluorine-containing diamond-like carbon, and conductive oxides such as ITO and IZO.

[0058] From the viewpoint of increasing the hardness of the laminate and improving the durability of the laminate, the inorganic substance-containing layer (1) is preferably a layer containing at least one of diamond-like carbon (DLC), silicon oxide, niobium oxide, silicon carbide oxide, and silicon carbide as an inorganic substance among the above, and more preferably a layer containing at least one of DLC, silicon oxide, and niobium oxide. Among these, the inorganic substance-containing layer is more preferably a DLC layer formed of diamond-like carbon (DLC). By using DLC, the film stress generated during the deposition of the inorganic substance-containing layer (1) tends to increase, making it easier to form a wrinkle structure.

[0059] [Cover resin layer] The cover resin layer is preferably formed on the resin layer by a dry process described later. The cover resin layer is a layer formed of a resin component and contains the resin component as a main component. Here, containing the resin component as a main component means that the resin component accounts for 50% by mass or more of the cover resin layer, preferably 70% by mass or more, preferably 80% by mass or more, preferably 90% by mass or more, and preferably 100% by mass.

[0060] As the resin component used for the cover resin layer, a resin component that can be formed on the resin layer by a dry process can be preferably used. Specific resin components include fluororesin, polyethylene, polystyrene, etc., and among them, a fluororesin layer formed by a fluororesin is preferred. By using a fluororesin, the cover resin layer can be easily formed on the resin layer by a dry process. In addition, by using a fluororesin, when the cover resin layer is the outermost surface, it becomes easier to impart chemical resistance, slipperiness, or liquid repellency to the laminate. Examples of the fluorine-based resin include polytetrafluoroethylene and tetrafluoroethylene-ethylene copolymer.

[0061] [Cover layer formation] The cover layer is preferably formed by a dry process as described below, but is not necessarily required to be formed by a dry process. If the cover layer is not formed by a dry process, unevenness, for example unevenness including a wrinkle structure, may be formed in the resin layer in advance by a separate dry process, and then the cover layer may be formed. When the cover layer is formed by a process other than the dry process, the inorganic substance and resin components used in the inorganic substance-containing layer and the cover resin layer may be other than those described above. Specifically, in addition to the resin components described above, the resin components exemplified as resin components usable in the overcover layer described below may be used.

[0062] [Cover layer thickness] The thickness (ta) of the cover layer is preferably 5 nm or more and 300 nm or less. By setting the thickness (ta) of the cover layer within the above range, a moderate film stress is generated when the film is formed by a dry process, and a moderate compressive stress is applied to the resin layer, making it easy to form irregularities having the desired roughness and structure. From the viewpoint of making it easy to form the desired irregularities on the outermost surface of the laminate, the thickness (ta) of the cover layer is more preferably 10 nm or more and 250 nm or less, and even more preferably 20 nm or more and 200 nm or less.

[0063] [Thickness ratio of cover layer to resin layer (ta / tb)] In the present invention, the ratio (ta / tb) of the thickness of the cover layer (ta, unit: nm) to the thickness of the resin layer (tb, unit: μm) is preferably 0.1 or more and 3500 or less. By setting the thickness ratio within the above range, when the cover layer is formed by a dry process, it is easy to form irregularities of a desired roughness by the dry process. In addition, when irregularities are formed on the surface of the resin layer before the cover layer is formed, the cover layer can prevent the unevenness from being smoothed. From the viewpoint of facilitating the formation of desired irregularities on the outermost surface of the laminate, the thickness ratio is more preferably 1 or more and 500 or less, more preferably 2 or more and 400 or less, and even more preferably 5 or more and 250 or less.

[0064] <Overcover layer> The overcover layer is a layer that is further provided on the cover layer. Examples of the overcover layer include an inorganic substance-containing layer and an overcover resin layer. The overcover layer can impart various functions to the outermost surface of the laminate by appropriately changing the material. The overcover layer may be a single layer, or two or more layers may be laminated. When two or more overcover layers are provided, for example, a combination of one or more inorganic substance-containing layers and one or more overcover resin layers may be used. In the following description, the inorganic substance-containing layer constituting the overcover layer may be referred to as inorganic substance-containing layer (2) to distinguish it from the inorganic substance-containing layer (1) constituting the cover layer described above.

[0065] [Inorganic-containing layer (2)] The inorganic substance-containing layer (2) is a layer formed of an inorganic substance and containing an inorganic substance as a main component. When the cover layer is the inorganic substance-containing layer (1), the inorganic substance-containing layer (2) may have a different composition from the inorganic substance-containing layer (1), for example, it may contain an inorganic substance different from the inorganic substance contained in the inorganic substance-containing layer (1). The inorganic substance-containing layer (2) is preferably formed of an inorganic substance that has good adhesion to the cover layer. In addition, the inorganic substance-containing layer (2) is preferably made of a material that can be formed on the cover layer by a dry process, but may also be made of a material that can be formed on the cover layer by a method other than the dry process.

[0066] The inorganic substance-containing layer (2) is preferably formed from a thin film containing at least one inorganic substance selected from diamond-like carbon (DLC), metal, metal oxide, metal nitride, metal carbide, or a composite thereof. The inorganic substance may further contain a fluoride such as calcium fluoride, or may contain fluorine as described later. In the inorganic substance-containing layer (2), examples of the metal constituting the metal, metal oxide, metal nitride, metal carbide, or a composite thereof include silicon, aluminum, zinc, titanium, niobium, gold, silver, copper, indium, tin, nickel, and the like. Among these, silicon and niobium are preferred, and silicon is more preferred.

[0067] The inorganic substance used in the inorganic substance-containing layer (2) is preferably at least one selected from silicon-based compounds such as silicon oxide, silicon nitride, silicon oxynitride, silicon oxide carbide, silicon oxycarbonitride, silicon carbide, fluorine-containing silicon oxide, and fluorine-containing silicon carbide; aluminum-based compounds such as aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxide carbide; niobium-based compounds such as niobium oxide; zinc-based compounds such as zinc oxide; titanium-based compounds such as titanium oxide; diamond-like carbon, fluorine-containing diamond-like carbon, and conductive oxides such as ITO and IZO.

[0068] Among the above, the inorganic substance-containing layer (2) is preferably a layer containing silicon carbide as an inorganic substance, that is, the inorganic substance-containing layer is preferably a silicon carbide layer using silicon carbide as an inorganic substance. By using silicon carbide, the hardness of the outermost surface of the laminate can be increased, and the heat resistance and durability of the laminate can be improved.

[0069] [Overcover resin layer] The overcover resin layer is a layer formed of a resin component and containing the resin component as a main component. When the cover layer is a cover resin layer, the overcover resin layer may have a different composition from the cover layer, for example, may contain a resin component different from the resin component contained in the cover resin layer. The resin component that can be used in the overcover resin layer is not particularly limited as long as it can adhere to the cover coat layer, and examples of the resin component include fluorine-based resins, silicone resins, acrylic resins, and epoxy resins.

[0070] Among the above, a fluororesin layer using a fluororesin is preferred. By using a fluororesin layer, it becomes easier to impart chemical resistance, slipperiness, or liquid repellency to the laminate. In addition, specific compounds of the fluororesin are as described above for the cover layer. By using these resins, the overcover resin layer can be formed by a dry process.

[0071] [Overcover layer thickness] The thickness of the overcover layer is not particularly limited as long as the irregularities formed by the resin layer appear on the outermost surface, but is preferably 5 to 300 nm, more preferably 10 to 250 nm, and even more preferably 20 to 200 nm.

[0072] <Method of manufacturing laminate> The laminate of the present invention may be produced by any production method, but a production method of a laminate according to one embodiment of the present invention includes the following steps 1 to 3. Step 1: A step of applying a curable resin composition to at least one surface of a substrate to form a resin layer precursor. Step 2: Semi-curing the resin layer precursor formed in step 1 Step 3: A step of further performing a surface treatment by a dry process on the resin layer precursor semi-cured in step 2 to form irregularities on one side of the surface of the substrate. However, step 2 may be omitted as described below, and therefore in step 3, the uncured resin layer precursor may be subjected to a surface treatment. Each step will now be described in more detail.

[0073] [Process 1] In step 1, a curable resin composition is applied to at least one surface of a substrate to form a resin layer precursor. The details of the curable resin composition used in step 1 are as described above. The curable resin composition may be diluted with a solvent such as water or an organic solvent as necessary. When diluted with a solvent such as water or an organic solvent, the amount of the curable resin composition described above (parts by mass, % by mass, etc.) and the amount of each component constituting the composition are based on the solid content. The organic solvent to be used is not particularly limited, and may be selected from the viewpoint of solubility, dispersibility, etc. depending on the composition of the curable resin composition. Examples of the organic solvent include alcohol-based solvents such as methyl alcohol, ethyl alcohol, isopropyl alcohol, etc.; ether-based solvents such as dimethyl glycol, ethylene glycol monoethyl ether, etc.; ester-based solvents such as ethyl acetate, etc.; acetate-based solvents such as propylene glycol monomethyl ether acetate, etc.; ketone-based solvents such as methyl isobutyl ketone, methyl ethyl ketone, etc.; aliphatic hydrocarbon-based solvents such as various alkanes, etc.; and aromatic hydrocarbon-based solvents such as toluene, xylene, benzene, etc. The organic solvent may be one type or two or more types, if necessary. The components constituting the curable resin composition may be dissolved in the solvent or may be dispersed in the solvent. When the curable resin composition is diluted with water, an organic solvent, or the like, it is preferable to adjust the solid content concentration to, for example, about 0.1% by mass or more and 50% by mass or less, preferably about 3% by mass or more and 40% by mass or less.

[0074] The curable resin composition can be applied to a substrate by any of the conventional coating methods such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, spray coating, dip coating, and spin coating. When the substrate is a resin film, the curable resin composition may be applied by in-line coating, which refers to applying the curable resin composition on the production line in which the resin film is formed. The solvent after coating can be dried by heating in an oven or by non-heating using a reduced pressure dryer. The surface of the substrate to which the curable resin composition is applied may be previously subjected to a surface treatment such as a corona treatment, a plasma treatment, or a UV ozone treatment.

[0075] [Process 2] In step 2, the curable resin composition in the resin layer precursor formed in step 1 is brought into a semi-cured state. The term "semi-cured" as used herein refers to a state in which the curable resin composition is not completely cured, and refers to a state in which the curing of the curable resin composition further progresses when further irradiated with active energy rays.

[0076] The purpose of semi-curing is to make the resin layer precursor obtained in step 1 in a state that is easy to handle before being brought into the vacuum drying process in step 3, and to control the uneven shape formed in step 3. Therefore, for example, if the resin layer precursor obtained in step 1 is very tacky and difficult to handle, it is preferable to perform a semi-curing treatment, but if there are no problems with handling, step 2 is not essential and irradiation with active energy rays may not be performed. Furthermore, by bringing the curable resin composition into a semi-cured state, the resin layer precursor is more likely to buckle during the surface treatment by the dry process in step 3, and projections and recesses having a desired structure are more likely to be formed.

[0077] In this step 2, the resin layer precursor formed in step 1 is irradiated with active energy rays to semi-cure the resin layer precursor. In the present invention, as described above, the curable resin composition does not contain an active energy ray polymerization initiator, or contains only a small amount of the active energy ray polymerization initiator. Therefore, the resin layer precursor is in a semi-cured state in which fluidity and curability remain in step 2. Therefore, shrinkage force is easily generated by the dry process described later, and the desired unevenness can be easily formed by controlling the semi-cured state.

[0078] The active energy rays used in step 2 may include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, and infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, and neutron beams. From the viewpoints of curing speed, availability of irradiation equipment, cost, and the like, curing by ultraviolet irradiation is advantageous. When the resin layer precursor is semi-cured by ultraviolet irradiation, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a xenon lamp, a chemical lamp, an electrodeless discharge lamp, an LED lamp, or the like that emits light in the wavelength range of 150 to 450 nm may be used. The ultraviolet light may be irradiated to such an extent that the resin layer precursor is semi-cured, and the irradiation amount is not particularly limited, but may be, for example, 0.5 to 5000 mJ / cm. 2 , preferably 1 to 2000 mJ / cm 2 It is sufficient to irradiate ultraviolet light with an integrated light quantity of about 100 nm.

[0079] [Process 3] In step 3, the semi-cured resin layer precursor or the uncured resin layer precursor in step 2 is further subjected to surface treatment by a dry process to form irregularities on one side of the surface of the substrate. In step 3, a cover layer may be formed by a dry process, but a dry process treatment without forming a film may be performed without forming a cover layer. In addition, the irregularities may be irregularities including a wrinkle structure. The dry process is a technique for performing a surface treatment on a semi-cured or uncured resin layer precursor under reduced pressure or in vacuum.

[0080] In this embodiment, the principle by which the unevenness including the wrinkle structure is formed by the surface treatment using a dry process is not clear, but is presumed to be as follows. When a cover layer is formed on a semi-cured or uncured resin layer precursor by a dry process, it is believed that the resin layer precursor receives energy from the dry process (light from plasma, radiant heat, electrons and ions, active radicals, or energy from incident particles) and hardens. At this time, the resin layer precursor that has received energy from the dry process heats up and shrinks while hardening, losing fluidity, and the cover layer grows, generating film stress. During this process, the compressive stress along the surface direction of the resin layer precursor increases, and it is estimated that buckling occurs when the resin layer precursor can no longer resist the compressive stress, forming a wrinkle structure. Furthermore, even in the case of a dry process that does not form a cover layer or involve film formation, it is presumed that the energy from the dry process treatment similarly generates compressive stress along the surface direction in the resin layer precursor, and when the resin layer precursor can no longer resist the compressive stress, buckling occurs and a wrinkle structure is formed.

[0081] The magnitude of the waviness in the wrinkle structure (i.e., surface roughness (Sa, Sz), specific surface area (S / A), Ssk value, etc.) is presumed to vary with the balance between the thickness of the resin layer and the cover layer, the hardness of the resin layer precursor in a semi-cured or uncured state, and the resin fluidity. Therefore, the magnitude of the waviness can be adjusted by appropriately changing the thickness of the resin layer and the cover layer, the components contained in the resin layer and the cover layer, the curing conditions, etc. Furthermore, the surface treatment by the dry process is for promoting the curing of the resin layer precursor as described above, and the resin layer may be fully cured, for example, in step 3. Full curing means a state in which curing does not substantially proceed even when the resin layer is irradiated with active energy rays.

[0082] In this manufacturing method, it is preferable to form the cover layer by surface treatment using a dry process. When the cover layer is formed by surface treatment using a dry process, membrane stress occurs as described above, making it easier to form a wrinkle structure. In addition, by forming the cover layer by surface treatment using a dry process, the cover layer can be formed while forming the unevenness in step 3, simplifying the process. Whether or not a dry process has been performed can be determined by observing the cross section with a SEM and / or a TEM. For example, if the cover layer is made of a crystalline material, if the crystal grain size changes in the thickness direction of the cover layer, it can be determined that a dry process has been performed. As the film formation by the dry process progresses, the crystal nuclei generated on the surface of the resin layer grow and the grain size gradually increases, so that the crystal grain size on the surface of the cover layer is the largest, and the crystal grain size tends to become smaller as it approaches the resin layer. On the other hand, such changes in crystal grain size are not observed when wet processing is performed by applying a solvent. In the case of wet processing, the solvent evaporates during the process of drying the coating, which tends to cause tiny voids throughout the thickness of the cover layer, resulting in a low-density film.

[0083] When the cover layer is formed by surface treatment using a dry process, examples of the surface treatment using the dry process include chemical vapor deposition (CVD) and physical vapor deposition (PVD). The dry process is preferably a process carried out under vacuum or reduced pressure. When the surface treatment is carried out under vacuum or reduced pressure, the semi-cured or uncured resin layer precursor is placed in an atmosphere with a low oxygen content, and oxygen inhibition that hinders radical polymerization is suppressed, so crosslinking proceeds, and the dry process facilitates curing. Therefore, when the dry process is carried out under vacuum or reduced pressure, a wrinkle structure is easily formed. The pressure in the dry process carried out under vacuum or reduced pressure depends on the method of the dry process, but is, for example, 15 Pa or less, preferably 10 Pa or less, and more preferably 1 Pa or less. The lower limit of the pressure in the dry process is not particularly limited, but considering the performance limit of each device, it is, for example, 1×10 -7 It is Pa.

[0084] The CVD is not particularly limited, and may be plasma CVD, thermal CVD, cat-CVD (catalyzed chemical vapor deposition), etc., but plasma CVD is preferred. By using plasma CVD, it becomes easier to form a wrinkle structure. From the viewpoint of facilitating the formation of a wrinkle structure, CVD is preferably performed under reduced pressure, and the pressure when forming the cover layer is preferably 15 Pa or less, more preferably 1×10 -2 Pa or more and 10 Pa or less, more preferably 1×10 -1 Pa or more and 1 Pa or less.

[0085] The output conditions when forming the cover layer are preferably 100 W or more and 1500 W or less, more preferably 300 W or more and 1200 W or less, and even more preferably 400 W or more and 1000 W or less, from the viewpoint of generating a necessary and sufficient film stress in the cover layer. The thickness of the cover layer can be adjusted by a known method. For example, when plasma CVD is used, the thickness can be adjusted by adjusting the output, pressure of the source gas, concentration of the source gas, plasma generation time, etc. When the surface treatment is carried out by CVD, the cover layer may be subjected to a crosslinking treatment by electron beam irradiation, if necessary, in order to improve water resistance and durability.

[0086] CVD is preferably used, for example, when forming an inorganic-substance-containing layer (1) or a cover resin layer, and can be particularly suitably used when forming an inorganic-substance-containing layer containing DLC ​​as an inorganic substance, an inorganic-substance-containing layer containing silicon carbide and / or silicon oxide as an inorganic substance, or a fluorine-based resin layer containing a fluorine-based resin or the like as a resin component.

[0087] Examples of PVD include vacuum deposition, sputtering, ion plating, etc., and among these, vacuum deposition and sputtering are preferred. PVD is suitable, for example, when the inorganic substance contained in the inorganic substance-containing layer (1) is a metal, a metal oxide such as niobium oxide or silicon oxide, or a metal nitride. Vacuum deposition is suitable when the inorganic substance contained in the inorganic substance-containing layer (1) is a metal such as gold, silver, copper, or aluminum, a metal oxide such as silicon oxide, titanium oxide, or aluminum oxide, or a fluoride such as calcium fluoride, while sputtering is suitable when the inorganic substance contained in the inorganic substance-containing layer (1) is a metal such as gold, silver, copper, or aluminum, or a metal oxide such as titanium oxide, aluminum oxide, niobium oxide, ITO, or IZO.

[0088] The pressure when forming the cover layer by PVD is preferably 1×10 -7 Pa or more and 20 Pa or less, more preferably 1×10 -6 Pa or more and 10 Pa or less, more preferably 1×10 -4 Pa or more and 5 Pa or less.

[0089] When the cover layer is formed by surface treatment using a dry process, a raw material for forming the cover layer may be appropriately selected and then the dry process may be carried out. For example, when forming an inorganic-containing layer containing DLC ​​as an inorganic material by CVD, it is preferable to use a hydrocarbon as a raw material. 4n+6 H 4n+12 (n is an integer of 1 or more), for example, alicyclic hydrocarbons such as adamantane, diamantane, triamantane, pentamantane, tetramantane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., aliphatic hydrocarbons such as acetylene, ethylene, propylene, methane, ethane, propane, etc., may be used. These raw materials may be used alone or in combination of two or more. The raw material gas may be used by diluting it with a rare gas such as argon (Ar) or helium (He). Of course, the inorganic material-containing layer (1) containing DLC ​​may be formed by PVD.

[0090] For example, when forming an inorganic-containing layer containing silicon carbide as an inorganic substance by CVD, it is preferable to use organosilanes such as tetramethylsilane and hexamethyldisilane as raw materials. Hydrogen gas may also be mixed into a mixed gas of a silicon component such as silane or disilane and a carbon component such as an alkane having 1 to 6 carbon atoms. However, other raw materials may be used as long as silicon carbide can be formed. Furthermore, for example, when a fluororesin layer is formed by CVD, a fluorine-based gas such as CF4, C2F4, C2F6, C3F8, C4F8, or C5F8 may be used as a raw material.

[0091] Furthermore, for example, when forming an inorganic-containing layer containing silicon carbide oxide as an inorganic material by CVD, a silicon compound (hereinafter also referred to as "silicon compound raw material") may be used as a raw material. The silicon compound raw material may be used in any state of gas, liquid, or solid at room temperature and normal pressure. In the case of gas, it may be introduced directly into the reactor (for example, the discharge space). In the case of liquid or solid, it may be vaporized by means of heating, bubbling, decompression, ultrasonic irradiation, or the like before use. It may also be used after dilution with a solvent, and the solvent may be an organic solvent such as methanol, ethanol, or n-hexane, or a mixture thereof.

[0092] Examples of the silicon compound raw material include silane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetra-t-butoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, phenyltriethoxysilane, (3,3,3-trifluoropropyl)trimethoxysilane, hexamethoxysilane, tetraisoprop ... Tyldisiloxane, bis(dimethylamino)dimethylsilane, bis(dimethylamino)methylvinylsilane, bis(ethylamino)dimethylsilane, N,O-bis(trimethylsilyl)acetamide, bis(trimethylsilyl)carbodiimide, diethylaminotrimethylsilane, dimethylaminodimethylsilane, hexamethyldisilazane, hexamethylcyclotrisilazane, heptamethyldisilazane, nonamethyltrisilazane, octamethylcyclotetrasilazane, tetrakis(dimethyla (amino)silane, tetraisocyanatosilane, tetramethyldisilazane, tris(dimethylamino)silane, triethoxyfluorosilane, allyldimethylsilane, allyltrimethylsilane, benzyltrimethylsilane, bis(trimethylsilyl)acetylene, 1,4-bistrimethylsilyl-1,3-butadiyne, di-t-butylsilane, 1,3-disilabutane, bis(trimethylsilyl)methane, cyclopentadienyltrimethylsilane, phenyldimethylsilane, phenyltrimethylsilane Examples of suitable methylsilane include methylsilane, propargyltrimethylsilane, tetramethylsilane, trimethylsilylacetylene, 1-(trimethylsilyl)-1-propyne, tris(trimethylsilyl)methane, tris(trimethylsilyl)silane, vinyltrimethylsilane, hexamethyldisilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, hexamethylcyclotetrasiloxane, and methyl silicate (for example, "Methyl Silicate 51" manufactured by Colcoat Co., Ltd.).

[0093] A cover layer may not be formed in the surface treatment by the dry process in step 3. The surface treatment in the case where a cover layer is not formed is not particularly limited as long as the resin layer precursor can be buckled by the surface treatment to form unevenness, and examples of the surface treatment include plasma treatment. The plasma treatment is not particularly limited, and may be performed by a method such as vacuum or reduced pressure plasma treatment, among which vacuum plasma treatment is preferred. The plasma treatment may be performed by converting a gas into plasma. Examples of the gas used include oxygen gas, hydrogen gas, nitrogen gas, and rare gases such as argon and helium. The gas may be one of these gases, or two or more types of gases may be mixed together. Among these, argon is preferred.

[0094] In this embodiment, the resin layer precursor that has not yet been sufficiently cured is subjected to surface treatment by a dry process as described above. Therefore, in order to stably form an uneven structure such as a wrinkle structure, it is preferable to adjust the time and storage temperature until the resin layer precursor is semi-cured (step 2) and then moved to the surface treatment by a dry process (step 3). The interval between step 2 and step 3 (i.e., the time from the end of the active energy ray irradiation to the start of the surface treatment by the dry process) is not particularly limited as long as the resin layer precursor is in a desired semi-cured state when the surface treatment is started, but is, for example, 24 hours or less, preferably 10 hours or less, and more preferably 5 hours or less. The lower limit of the interval is not particularly limited, and it may be 0 minutes or more. The interval between step 2 and step 3 is not particularly limited, but the substrate on which the resin layer precursor is formed may be left at a temperature of, for example, 0°C or higher and 40°C or lower, preferably 5°C or higher and 30°C or lower. Furthermore, when the interval time is long, the conditions for irradiating the active energy rays in step 2 may be appropriately selected, taking into consideration that curing progresses between step 2 and step 3.

[0095] In the present manufacturing method, by carrying out the above steps 1 to 3, or steps 1 and 3, a resin layer, or a resin layer and a cover layer, is formed on the substrate, and irregularities including a wrinkle structure can be formed on the surface of the resin layer or the surface of the cover layer.

[0096] [Step 4] This production method may further include the following step 4 after the above steps 1 to 3, or after steps 1 and 3. Step 4: A step of forming a cover layer on one side of the substrate surface-treated in step 3, or forming an over-cover layer on the cover layer formed by the surface treatment. Since the present manufacturing method includes step 4, a cover layer can be formed on the resin layer that has been subjected to the above-mentioned surface treatment, or an overcover layer can be formed if a cover layer already exists.

[0097] In step 4, the cover layer or overcover layer can be formed by the same method as the method for forming the inorganic-substance-containing layer and the resin layer in step 3, that is, the inorganic-substance-containing layer and the resin layer can be formed by a surface treatment using a dry process. Specific explanations of the method for forming each of these layers are as explained in step 3, and therefore will not be repeated. In step 4, the cover layer or overcover layer can also be formed by a method other than the dry process. For example, a coating liquid containing an inorganic substance, a resin component, or an inorganic substance and a resin component can be applied to one side of the substrate to form a coating film, and the coating film can be dried, cured, or the like as necessary.

[0098] <Applications of laminates> The laminate of the present invention can be suitably used for packaging food, daily necessities, industrial products, medicines, etc. Specifically, it can be used as packaging materials such as various containers, such as bottle containers and pouch containers, for food, cosmetics, daily necessities such as shampoo and rinse, medicines, various industrial products, etc., and films. In packaging materials, it can be suitably used as a component for preventing adhesion of contents by imparting water repellency and oil repellency. The laminate can also be used as an optical material. Examples of optical materials include window glass, lenses, substrates, etc. In optical materials, the haze and light transmittance of the optical material can be controlled by imparting cloudiness to the optical material through unevenness such as a wrinkle structure.

[0099] The laminate of the present invention may have a coating layer on the resin layer, cover layer or overcover layer that is the outermost surface of the laminate, depending on the application, to the extent that the effect of the present invention is not impaired. For example, in an application for preventing adhesion, the surface of the laminate can be provided with anti-adhesion properties by providing a coating layer having a liquid repellent effect.

[0100] <Explanation of terms> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". EXAMPLES

[0101] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples in any way. The measurement and evaluation methods used in the present invention are as follows.

[0102] (1) Method for measuring the thickness of the resin layer The surface of the resin layer was stained with RuO4 and embedded in epoxy resin. Then, sections prepared by ultrathin sectioning were stained again with RuO4, and the cross section of the resin layer was measured using a TEM (Hitachi High-Technologies Corporation "H-7650", accelerating voltage 100 kV). The thickness was determined as the average value of the maximum thickness and the minimum thickness.

[0103] (2) Method for measuring the thickness of the cover layer Samples were prepared by epoxy resin embedding ultrathin sectioning and measured using a cross-sectional TEM (JEM-1200EXII, manufactured by JEOL Ltd.) at an accelerating voltage of 120 kV.

[0104] (3) Sa (arithmetic mean roughness), Sz (maximum height), and specific surface area (S / A) The Sa, Sz, and specific surface area (S / A) of the outermost surface of the laminate were measured using a three-dimensional non-contact surface shape measuring device (VertScan2.0 R5200G, manufactured by Ryoka Systems Co., Ltd.) The measurements were performed in an area of ​​94.33 μm × 70.75 μm using a 50x objective lens.

[0105] (4) Measurement of bias The deviation degree Ssk of the outermost surface of the obtained laminate was measured according to ISO25178 and the method described in the specification.

[0106] (5) Haze value The haze value (%) was measured in accordance with JIS K7136:2000 using a haze meter ("NDH5000" manufactured by Nippon Denshoku Industries Co., Ltd.).

[0107] (6) Surface observation The outermost surface of the laminate on one side of the substrate was observed with a 50x objective lens using the above-mentioned three-dimensional non-contact surface shape measuring device to obtain a three-dimensional observation image of 94.33 μm × 70.75 μm. Each observation image was rated as A (good) if irregular wrinkle-like unevenness (unevenness with a wrinkle structure) was observed, and B (poor) if no irregular wrinkle-like unevenness was observed. In addition, for Examples 1 to 4 and Comparative Examples 2, 4, and 5, the obtained three-dimensional images are shown in FIGS.

[0108] Example 1 (Preparation of active energy ray curable resin composition (AC)) 99.5 parts by mass of a fluorene-based bifunctional acrylate (manufactured by Osaka Gas Chemicals Co., Ltd., product name "Oxol EA-0250P") as an active energy ray-polymerizable compound and 0.5 parts by mass of an active energy ray polymerization initiator (IGM Resins BV, product name "Omnirad184", 1-hydroxycyclohexyl-phenyl ketone) were added to and dissolved in a solvent, methyl isobutyl ketone (MIBK), to a solids concentration of 10% by mass, to obtain a diluted solution of an active energy ray-curable resin composition.

[0109] (Formation of resin layer precursor) The obtained diluted solution of the active energy ray-curable resin composition (AC) was applied onto one side of a PET film (manufactured by Mitsubishi Chemical Corporation, product name "T100 type", thickness 188 μm) as a substrate so that the thickness after drying would be as shown in Table 1, and the film was dried by heating at 80°C for 1 minute. Thereafter, the film was exposed to ultraviolet light from a high-pressure mercury lamp using an ultraviolet irradiation device (manufactured by Ushio Inc.) with an integrated light amount of 427 mJ / cm. 2 The resin layer precursor was irradiated and cured to form a semi-cured resin layer precursor. The surface of the semi-cured resin layer precursor was only slightly sticky. After that, the resin layer precursor was left at room temperature (23°C) for 3 hours, and then the vacuum deposition described below was immediately started.

[0110] (Formation of cover layer) Using a vacuum deposition apparatus (manufactured by ULVAC, Inc.), vacuum deposition was performed using silicon oxide as a deposition source to form an inorganic-containing layer (1) (silicon oxide (SiOx) layer) having a thickness of 50 nm on the semi-cured resin layer precursor, thereby obtaining a laminate having a laminate structure of substrate / resin layer / cover layer.

[0111] Example 2 The cover layer was formed in the same manner as in Example 1, except that the cover layer was a DLC layer, by the following method. (Formation of cover layer) Using a plasma CVD device (manufactured by U-TECH Co., Ltd.), acetylene gas was introduced to set the partial pressure to 1 Pa, and CVD was performed at a power of 500 W under a vacuum of 1 Pa to form an inorganic substance-containing layer (1) (DLC layer) having a thickness of 100 nm on the semi-cured resin layer precursor, thereby obtaining a laminate having a laminate structure of substrate / resin layer / cover layer.

[0112] Examples 3 and 4 Except for not blending the active energy ray polymerization initiator into the active energy ray curable resin composition, the same procedure as in Examples 1 and 2 was carried out. Note that the surface of the semi-cured resin layer precursor was somewhat sticky.

[0113] Comparative Example 1 The laminate of Comparative Example 1 was prepared by using a substrate made of a PET film (manufactured by Mitsubishi Chemical Corporation, product name "T100 type", thickness 188 μm).

[0114] Comparative Example 2 The same procedure as in Example 1 was carried out, except that the formation of the resin layer precursor was omitted and a laminate having a laminate structure of a substrate / cover layer was obtained.

[0115] Comparative Example 3 The same procedure as in Example 1 was carried out except that the active energy ray curable resin composition was changed to 97.0 parts by mass of the active energy ray polymerizable compound and 3.0 parts by mass of the active energy ray polymerization initiator, and the formation of the cover layer was omitted to obtain a laminate having a laminated structure of the substrate / resin layer. Note that the surface of the resin layer after the active energy ray irradiation was not sticky.

[0116] Comparative Examples 4 and 5 The same procedures as in Examples 1 and 2 were carried out, except that the active energy ray-curable resin composition was formulated to contain 97.0 parts by mass of the active energy ray-polymerizable compound and 3.0 parts by mass of the active energy ray polymerization initiator.

[0117] [Table 1]

[0118] As shown in Table 1, in each example, a resin layer precursor formed from an active energy ray-curable resin composition was irradiated with active energy rays, and then a surface treatment was performed by a dry process, thereby forming unevenness including a wrinkle structure on the outermost surface of the laminate. This is presumably because the active energy ray-curable resin composition does not contain an active energy ray polymerization initiator or contains a small amount of such an initiator, and therefore a resin layer precursor that is appropriately semi-cured by irradiation with active energy rays can be obtained, and therefore sufficient curing shrinkage force is generated by surface treatment by the dry process.

[0119] On the other hand, in Comparative Examples 1 to 3, since a resin layer was not formed or the resin layer was not subjected to surface treatment by a dry process, it was not possible to form unevenness including a wrinkle structure on the outermost surface of the laminate. Furthermore, in Comparative Examples 4 and 5, even when surface treatment was performed by a dry process, unevenness including a wrinkle structure could not be formed on the outermost surface of the laminate. This is presumably because the active energy ray-curable resin compositions of Comparative Examples 4 and 5 contained more than 2.5% by mass of active energy ray polymerization initiator, and therefore curing proceeded sufficiently by irradiation with active energy rays, causing loss of fluidity, and therefore sufficient curing shrinkage force was not generated even when surface treatment was performed by a dry process.

[0120] In addition, as is clear from the comparison of Examples 1 to 4, the size of the unevenness can be controlled by the presence or absence of an active energy ray polymerization initiator and by the difference in the dry process, and an uneven structure suitable for various applications (adhesion prevention, light transmittance, etc.) utilizing fine unevenness on the surface can be formed. Note that, in Examples 1 and 2, by including a trace amount of an active energy ray polymerization initiator, the resin layer precursor after energy ray irradiation had a weak surface stickiness and was excellent in handleability. [Explanation of symbols]

[0121] 10 Laminate 10A Outer surface of laminate 11 Base material 11A One side of the substrate 12 Resin layer 13 Cover Layer 14 Overcover Layer

Claims

1. A substrate and a resin layer provided on at least one surface of the substrate, the resin layer is formed from an active energy ray-curable resin composition, the outermost surface of the laminate on the one surface side of the base material has an unevenness with a wrinkle structure, The active energy ray-curable resin composition does not contain an active energy ray polymerization initiator or contains an active energy ray polymerization initiator in an amount of 2.5 mass% or less, the outermost surface has an arithmetic mean roughness (Sa) of 1,300 nm or less and a specific surface area (S / A) of 1.0031 or more; A cover layer which is an inorganic substance-containing layer is further provided on the resin layer, and the cover layer is formed as a layer on the resin layer in direct contact therewith; A laminate, wherein the inorganic substance-containing layer is formed from at least one material selected from the group consisting of DLC, metal oxides, metal nitrides, metal carbides, and composites thereof.

2. The laminate according to claim 1 , wherein the active energy ray is ultraviolet light.

3. 3. The laminate according to claim 1, wherein the outermost surface has an arithmetic mean roughness (Sa) of 50 nm or more.

4. The laminate according to any one of claims 1 to 3, wherein the cover layer has a thickness (ta) of 5 nm or more and 300 nm or less.

5. A step of applying an active energy ray-curable resin composition to at least one surface of a substrate to form a resin layer precursor; a step of semi-curing the resin layer precursor formed by the coating by irradiating it with active energy rays; a step of further performing a surface treatment on the semi-cured resin layer precursor by a dry process to form irregularities having a wrinkle structure on one surface of the substrate; Equipped with The active energy ray-curable resin composition does not contain an active energy ray polymerization initiator or contains an active energy ray polymerization initiator in an amount of 2.5 mass% or less, A method for producing a laminate, wherein a specific surface area (S / A) of an outermost surface of the laminate on the one surface side of the substrate is 1.0031 or more.

6. The method for producing a laminate according to claim 5 , wherein the cover layer is formed by the dry process.

7. The method for producing a laminate according to claim 5 or 6, wherein the surface treatment is any one of chemical vapor deposition, physical vapor deposition, and plasma treatment.

Citation Information

Patent Citations

  • Resin composition for formation of matte surface and method for forming matte surface

    JP1997053024A

  • Electrode substrate for reflection type liquid crystal display device and its production

    JP2000284302A

  • Film and method for manufacturing the same

    JP2011140190A

  • Decorating method with lame pattern and decorative structure with lame pattern

    JP2014008470A

  • Gas barrier film and method of producing the same

    JP2015093412A